Benthic Macroinvertebrates as Indicators of Organic Pollution in Upstream Batena River, Hossana, Central Ethiopia - Wanore, Denebo Sebaro; Ordise, Tigist Markos; Munye, Haymanot Teshale; Dawore, Freheywot Danecho; Heramo, Getahun Lega (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Benthic macro invertebrates are insects and other organism without a back bone that can be seen without magnification and that live in the bottom of all water bodies. They are bio monitor species in determining the water quality in fresh water and other aquatic ecosystems as they are indicator of environmental change of aquatic ecosystem and fresh water ecosystem. The aim of this study was to assess Organic pollution by using benthic macro invertebrate as indicator in upstream parts of Batena River and implication to the water quality of the river. Benthic Macro invertebrates were collected using Scrubber net and sieve with mesh size of 1mm. A total of 57 individual within 4 families belong to 4 orders and one class was identified during the study period. Most dominant group was Hemiptera 29(50.8%), Diptera14 for Chironomidae (Red) (24.56%) and for Diptera family chironomidae (Pale) (19.3%). Sphendiea, Psephyendiea and class of Turbilaria accounts the same percentage (1.75%) and their total abundance was also similar. The pollution level of the river was assessed using Hillsenhoff Family Biotic Index (HFBI) and the value was 7.96. Over all study showed that the river is polluted and have poor water quality as result of diverse Organic pollutant agents. Therefore, the local people and administration of the river should work hard to prevent further deterioration of the river quality by raising public awareness, prevention of waste disposal and treat the waste water before discharging it directly to the river.